VALIDASI ST EUROPEAN QUALITY OF LIFE-5 DIMENSIONS (EQ-5D) VERSI INDONESIA PADA PASIEN HIPERTENSI DI PUSKESMAS KOTAGEDE II YOGYAKARTA - Sari, Andriana; Yuni Lestari, Nidia; Aryani Perwitasari, Dyah (Pharmaciana, 2015)
Hypertension is a major risk factor for the occurrence of deaths from non-communicable diseases in the world. In the World Health Statistics 2012, WHO reported that approximately 51% of deaths from stroke and 45% of coronary heart disease due to hypertension. Patients with obsesitas, hypertension, and diabetes can worsen patientâs quality of life both physically and mental status. This study aims to assess the quality of life by the European Quality of Life-5 Dimensions (EQ-5D) questionnaire. This study aims to determine the validity and reliability of the EQ-5D in Indonesian version as an instrument for measuring the quality of life of patients with hypertension in the Health Center Kotagede II Yogyakarta. The method of this study was descriptive observational. Data were collected using a questionnaire conducted at a particular time. The instrument used in this study is the EQ-5D which has been translated into Indonesian. Affordable population in this study were all patients with hypertension in Health Center Kotagede II Yogyakarta at May to June 2014. The sample in this study are in accordance with the criteria for inclusion and exclusion criteria. Analysis of the validity was constructs validity with Pearson method. Test reliability was Cronbachs alpha coefficient. From the data analysis for 51 patients Hypertension Pearson correlation coefficient obtained results are above 0.30, so it can be concluded instrument EQ-5D questionnaire Indonesian version is valid. Results CornbachsÎ± is 0718 so it can be concluded instrument EQ-5D questionnaire Indonesian version is reliable.